2021
DOI: 10.21203/rs.3.rs-286146/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Outcome of SARS-CoV-2 Infection in 121 Patients With Inborn Errors of Immunity: A Cross-sectional Study

Abstract: Purpose: There is still scarce data on SARS-CoV-2 infection in patients with Inborn Errors of Immunity (IEI) and many questions. We aimed to describe the clinical outcome of SARS-CoV-2 infection in Brazilian IEI patients and to identify factors influencing the outcome of infection.Methods: We did a cross-sectional, multicenter study that included patients of any age affected by IEI and SARS-CoV-2 infection. The variables studied were sex, age, type of IEI, comorbidities (number and type), treatment in use for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
64
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(68 citation statements)
references
References 42 publications
3
64
1
Order By: Relevance
“…We here analyze the published case series and single cases describing the outcome of COVID-19 in patients with IEIs. Removing duplicate patients, to the best of our knowledge, we count a total of 649 reported patients with IEI who were infected with SARS-CoV-2, spanning all subgroups of immune defects as defined by the International Union of Immunological Societies committee for IEI (Table 1 ) [ 1 ▪▪ , 3 , 4 , 5 ▪ , 9 ▪ , 10 65 ]. Patients were mostly included based on a positive molecular test, antigenic test, or serology, although some reports also include patients with symptoms and clinical imaging compatible with a diagnosis of COVID-19, with or without a history of exposure to infected individuals [ 10 , 12 , 14 , 15 , 18 ].…”
Section: Overview Of Reports Of Coronavirus Disease 2019 In Patients With Inborn Errors Of Immunitymentioning
confidence: 99%
See 2 more Smart Citations
“…We here analyze the published case series and single cases describing the outcome of COVID-19 in patients with IEIs. Removing duplicate patients, to the best of our knowledge, we count a total of 649 reported patients with IEI who were infected with SARS-CoV-2, spanning all subgroups of immune defects as defined by the International Union of Immunological Societies committee for IEI (Table 1 ) [ 1 ▪▪ , 3 , 4 , 5 ▪ , 9 ▪ , 10 65 ]. Patients were mostly included based on a positive molecular test, antigenic test, or serology, although some reports also include patients with symptoms and clinical imaging compatible with a diagnosis of COVID-19, with or without a history of exposure to infected individuals [ 10 , 12 , 14 , 15 , 18 ].…”
Section: Overview Of Reports Of Coronavirus Disease 2019 In Patients With Inborn Errors Of Immunitymentioning
confidence: 99%
“…Reflecting the relative frequency of humoral immunodeficiencies among IEIs, the majority of patients who experienced COVID-19 are affected by antibody deficiency ( n = 330, 51%) [ 5 ▪ , 9 ▪ , 10 , 12 17 , 19 , 24 , 26 , 28 , 30 , 33 , 34 , 36 , 37 , 42 , 44 , 45 , 48 , 52 , 53 , 55 , 57 – 62 , 64 , 66 69 ]. Among them, 200 have common variable immunodeficiency (CVID, 60% of all antibody deficiencies), 59 have X-linked agammaglobulinemia (XLA, 18%) and eight have autosomal recessive agammaglobulinemia (2%).…”
Section: Overview Of Reports Of Coronavirus Disease 2019 In Patients With Inborn Errors Of Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…Some groups of immunocompromised patients are at increased risk for severe SARS-CoV-2 infection. 1,2 For patients with inborn errors of immunity (IEIs), some studies have reported an infection fatality rate similar to that in the general population, 3,4 but others have documented increased hospitalization and death rates [5][6][7][8] along with younger age at death and prolonged SARS-CoV-2 positivity. 4,5 The nature of the underlying gene defect and associated immunopathology may be important predictors of disease severity and outcome.…”
Section: Introductionmentioning
confidence: 99%
“…National epidemiological studies tend to consider immunocompromised individuals as a homogenous group (e.g., HIV-1 infection, solid organ transplant, immunosuppressive medications) and are unable to inform our understanding of outcome in individuals with rare diseases [1,2]. Instead, retrospective case series have been used to develop our understanding of the risk in patients with PID and SID [3][4][5][6][7][8][9]. While the results of such studies must be interpreted with caution, a consistent pattern has emerged showing that adult patients with PID and SID are at an increased risk of morbidity and mortality from COVID-19 compared to the general population, and that an increased prevalence of chronic co-morbidities, potentially driven by underlying immunode ciency, partially contributes to that risk.…”
Section: Introductionmentioning
confidence: 99%